2008
DOI: 10.1016/j.brainres.2008.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating frontal and parietal contributions to spatial working memory with repetitive transcranial magnetic stimulation

Abstract: Functional neuroimaging studies have produced contradictory data about the extent to which specific regions of the frontal and the posterior parietal cortices contribute to the retention of information in spatial working memory. We used high frequency repetitive transcranial magnetic stimulation (rTMS) to assess the necessity for the short-term retention of spatial information of brain areas identified by previous functional imaging studies: dorsolateral prefrontal cortex (dlPFC), frontal eye fields (FEF), sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 54 publications
8
77
3
Order By: Relevance
“…This is consistent with previous fMRI studies which showed that the abstract reasoning performance significantly activated the SPL region (Goel et al, 2000;Goel & Dolan, 2001;Knauff et al, 2002Knauff et al, , 2003. In general, SPL is associated with spatial processing based on evidence from fMRI (Takahama et al, 2010;Thakral & Slotnick, 2009), neurological patients (Ferber & Danckert, 2006;Shinoura et al, 2009) and TMS studies (Hamidi et al, 2008(Hamidi et al, , 2009. Some authors have claimed that cognitive processes of constructing and manipulating spatially organized mental models are essential for deductive reasoning (Johnson-Laird, 1999, 2001.…”
Section: The Role Of Spl In Abstract Reasoningsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with previous fMRI studies which showed that the abstract reasoning performance significantly activated the SPL region (Goel et al, 2000;Goel & Dolan, 2001;Knauff et al, 2002Knauff et al, , 2003. In general, SPL is associated with spatial processing based on evidence from fMRI (Takahama et al, 2010;Thakral & Slotnick, 2009), neurological patients (Ferber & Danckert, 2006;Shinoura et al, 2009) and TMS studies (Hamidi et al, 2008(Hamidi et al, , 2009. Some authors have claimed that cognitive processes of constructing and manipulating spatially organized mental models are essential for deductive reasoning (Johnson-Laird, 1999, 2001.…”
Section: The Role Of Spl In Abstract Reasoningsupporting
confidence: 89%
“…The second aim of the present study was to demonstrate recent findings of rTMS studies in our laboratory which elucidated the roles of the inferior frontal cortex (IFC) and the superior parietal lobule (SPL) in human deductive reasoning (Tsujii et al, 2010a(Tsujii et al, , 2011a. Especially, we adopted an off-line rTMS method in which lowfrequency rTMS is delivered to a specific brain area over several minutes to disrupt normal functioning of this area transiently after stimulation (Devlin et al, 2003;Hamidi et al, 2008Hamidi et al, , 2009Hilgetag et al, 2001;Miller et al, 2008;Robertson et al, 2003). We investigated the effect of off-line rTMS of IFC and SPL on subsequent reasoning performance of congruent and incongruent trials.…”
Section: Fig 1 Materials Design Of the Belief-bias Effectmentioning
confidence: 95%
“…The fibers of SLF II pathway has been demonstrated that it originates from the prefrontal cortex and runs back to the posterior parietal region in humans [20]. Previous studies have reported executive function [31]and working memory [32] were associated with these regions. In addition, Trail Making Test is believed to involve multiple cognitive functions [33,34].…”
Section: Discussionmentioning
confidence: 97%
“…Despite traditional theories emphasizing parietal contributions to spatial attention and sensorio-motor integration (50), significant parietal lobe activation has been also observed in previous eventrelated potentials (51,52) and functional neuroimaging studies during the performance of memory retrieval tasks (53)(54)(55)(56)(57)(58). Our greater activated network including the precuneus, medial, and lateral parietal cortex may be associated with the correct recognition of information (17,59,60); particularly, these regions may subserve temporal structures in order to resolve external interference and accomplish a successful recognition judgment.…”
Section: Age-related Changes In Neural Patterns At Recognition As a Cmentioning
confidence: 99%